2009
DOI: 10.3233/cbm-2009-0119
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum Her2/neu, BCL2, CA15-3 and CEA in breast cancer patients: A short follow-up

Abstract: Serum Her2/neu, BCL2, CA15-3 and CEA in breast cancer patients were useful markers for predicting aggressive behavior of tumor and elevated serum levels are associated with breast cancer relapse. Our relatively small study population limits the predictive power of the panels presented here, but the benefits of a serum biomarker and multimarker approach are clearly illustrated and further studies utilizing larger clinical cohorts are well warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 34 publications
5
33
0
3
Order By: Relevance
“…This finding is in acordance with the results of Samy et al . [46], who found that preoperative serum levels of CA15-3 and CEA were significantly higher in breast cancer patients compared with the levels of the control group, and these markers decreased after operation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in acordance with the results of Samy et al . [46], who found that preoperative serum levels of CA15-3 and CEA were significantly higher in breast cancer patients compared with the levels of the control group, and these markers decreased after operation.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several other studies have also elaborated on the independent negative impact of these serum markers on the prognosis of the patients with breast cancer. Elevated serum levels of HER2 were associated with several factors related to tumor aggressiveness of breast cancer, such as tumor size, advanced stage, lymph node involvement, poor histological differentiation and shorter disease free and/or overall survival (Azizun-Nisa et al, 2008;Samy et al, 2010;Kong et al, 2012;Ma et al 2012;Wang et al, 2012). Sharif et al (2010) showed a positive association of Her-2 immunohistochemical expression with tumour size and lymph node metastasis only in post-menopausal women, indicating an age-related association of Her-2 expression with the histological prognostic markers in breast carcer.…”
Section: Discussionmentioning
confidence: 99%
“…[2324] Although advances in immunohistochemistry are very promising, there is still much work that needs to be done to characterize metastases. [252627] A recent letter to the editor highlights the pitfalls that can occur when differentiating primary cutaneous apocrine carcinoma from a metastasis. [28] Although cytokeratin 5/6 is associated with cutaneous apocrine carcinoma, this staining pattern has also been noted with metastatic squamous cell carcinoma [Figure 3c].…”
Section: Diagnosis and Immunohistochemistrymentioning
confidence: 99%